Associations between effort, importance, and self‐monitoring during and after a 12‐week behavioural weight management program - Abraham Eastman; Brittney N. Dixon; Kathryn M. Ross (Obesity Science & Practice, 2020)
Summary Objective Self‐monitoring of weight and caloric intake has been associated with improved weight loss and weight loss maintenance in behavioural weight loss programs; however, participants' adherence to self‐monitoring tends to decrease over time. To identify potential barriers to self‐monitoring adherence, the current study examined week‐to‐week associations between ratings of perceived effort, relative importance of weight loss goals, and adherence to self‐monitoring of weight and caloric intake during and after a behavioural weight loss programme. Method Participants were 74 adults with overweight and obesity enrolled in a 12‐week, Internet‐based weight loss programme followed by a 40‐week “maintenance” period during which no additional intervention was provided. Participants self‐reported adherence to self‐monitoring and completed ratings of effort and importance on a study website weekly throughout the study period (1 year). Results Longitudinal multilevel models demonstrated that higher ratings of effort were associated with fewer days of self‐monitoring of weight, β = −0.100, p < .0001, and caloric intake, β = −0.300, p < .0001. Conversely, higher ratings of importance were associated with more frequent self‐monitoring of weight, β = 0.360, p < .0001, and caloric intake, β = 0.742, p < .0001. Moreover, the magnitude of these associations were stronger during the maintenance period than during initial intervention, ps < .01. Conclusions Perceptions of effort and importance are both independently associated with adherence to self‐monitoring weight and caloric intake, and this effect appears to be stronger after the end of initial intervention. Future research should investigate whether tailoring intervention content based on these constructs can improve adherence to self‐monitoring.